1983
DOI: 10.1111/j.1432-1033.1983.tb07330.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Homologous Cytochromes b5 in a Single Cell

Abstract: The amino acid sequence of the heme-binding domains of rat liver cytochromes b, from outer mitochondria1 membranes and from microsomes has been determined by a combination of automatic and manual degradation of fragments generated by trypsin digestion and by cleavage at tryptophan. Tryptic peptides were separated by high-pressure liquid chromatography.The sequence of microsomal cytochrome b, is identical with the one published by 0201s and Heinemann after completion of this study [Biochinz. Biophj,~. Artu (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Proteins of this class, which have been called tailanchored (TA) (Kutay et al, 1993), lack an N-terminal signal sequence and reach their destination within the cell by posttranslational mechanisms Kutay et al, 1993). TA proteins identified on the MOM include the protooncogene bcl-2 (Akao et al, 1994), the mitochondrial isoform of cytochrome b(5) [outer membrane b(5) or OM b(5); Lederer et al, 1983;D'Arrigo et al, 1993], TOM components TOM 5 and 6 (Neupert, 1997), a synaptojanin binding protein (Nemoto and De Camilli, 1999), an alternatively spliced isoform of vesicle associated membrane protein, VAMP-1B (Isenmann et al, 1998). An important problem is the mechanism through which these proteins discriminate between the MOM and the endoplasmic reticulum (ER) membrane, because the latter is the target for many polypeptides with similar topology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins of this class, which have been called tailanchored (TA) (Kutay et al, 1993), lack an N-terminal signal sequence and reach their destination within the cell by posttranslational mechanisms Kutay et al, 1993). TA proteins identified on the MOM include the protooncogene bcl-2 (Akao et al, 1994), the mitochondrial isoform of cytochrome b(5) [outer membrane b(5) or OM b(5); Lederer et al, 1983;D'Arrigo et al, 1993], TOM components TOM 5 and 6 (Neupert, 1997), a synaptojanin binding protein (Nemoto and De Camilli, 1999), an alternatively spliced isoform of vesicle associated membrane protein, VAMP-1B (Isenmann et al, 1998). An important problem is the mechanism through which these proteins discriminate between the MOM and the endoplasmic reticulum (ER) membrane, because the latter is the target for many polypeptides with similar topology.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cyt b(5) exists in two homologous isoforms (Lederer et al, 1983), which are localized specifically to the MOM [OM b(5)] or to the ER [ER b(5)], with hardly any overlap between the two distributions . Work in our laboratory showed that the tail region of OM b(5) contains the information for localization to the MOM (De Silvestris et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although these similarities in the targeting signals allow some TA proteins to exhibit dual localization within the cell, most TA proteins are targeted exclusively to one organelle or the other . Notably, only mammalian cells have been shown to contain two distinct isoforms of Cb5 that are localized specifically to the ER or to the mitochondrial outer membrane (Ito, 1980;Lederer et al, 1983;D'Arrigo et al, 1993). Despite intensive efforts over the past few years, details related to the nature of the cellular machinery involved in targeting and membrane integration of TA proteins to either ER or mitochondrial membranes in any organism have not been resolved (reviewed in Borgese et al, 2003; for an alternate point of view, see Abell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the reductase in its various locations is molecularly identical (Meldolesi et al, 1980). Two distinct forms of cytochrome b 5 have been shown to exist in rat liver (Lederer et al, 1983). Cytochrome b 5 localized in the outer mitochondrial membrane is distinguishable from the microsomal form in spectral and immunological properties as well as in primary structure.…”
Section: Tablementioning
confidence: 98%